COUNSELING AND EDUCATION ON THE USE OF BETEL LEAVES AS A NATURAL ANTISEPTIC AMONG ADOLESCENTS OF SMA DDI MAROS - Sulastri; muliana hafid; Muhammad Farid; Muhammad Aris; Ariyani Buang; Andi Nurilmi Adriana; Anita; Wahyudin Rauf (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2026)
The use of natural ingredients as an alternative antiseptic is gaining increasing attention as public awareness of the use of safe, readily available, and economical products increases. One plant that has great potential as a natural antiseptic is the betel leaf (Piper betle L.), which is known to contain active compounds such as flavonoids, tannins, saponins, and essential oils that have antibacterial and antiseptic properties. This community service activity aims to increase the knowledge and understanding of adolescents regarding the benefits of betel leaves as a natural antiseptic through counseling and education for DDI Maros High School students. The implementation method includes the preparation stage, material counseling, simple demonstrations of the use of betel leaves, interactive discussions, and evaluation of participant understanding through questions and answers. The activity was carried out using a participatory approach that actively involved students in each learning session. The results of the implementation showed an increase in participant knowledge regarding the content, benefits, and how to use betel leaves as a natural antiseptic. In addition, participants showed high enthusiasm throughout the activity, marked by active participation in the question and answer session and demonstrations. This counseling made a positive contribution in raising adolescent awareness of the importance of using traditional medicinal plants as a preventive measure in maintaining cleanliness and health. Through this activity, it is hoped that students will be able to apply the knowledge they gain in their daily lives and become agents of health education in their schools and communities. Similar programs need to be implemented on an ongoing basis to broaden the younger generation's understanding of the local wisdom-based uses of herbal plants.